Status Gizi Penerima PMT Pemulihan dan Penerima PMT Penyuluhan pada Penderita Gizi Buruk, Studi di Kabupaten Jepara - Sarimah Sarimah; Sihol P Hutagalung (JURNAL RISET GIZI, 2013)
Background : Malnutrition in early life may cause low quality of live; thus supplementary feeding or educational feeding programs are needed.Objective :The objective of this study  was to analyze the nutritional status difference among malnourished children after receiving suplementary feeding  and educational feeding program.Method : The Subject  of the study were of 90 children under five consisting of 45 samples from sub  distric Kembang and 45 samples from sub distric Bangsri. Using Repeated Measure Anova SPSS program, test was used to know the difference nutritional status of the sample after one month, two months, three months giving of suplementary feeding both for the samples group of recovery suplementary feeding  and education suplementary feeding receiver, and Independence Test of T – test to know the difference nutritional status between the samples group of recovery suplementary feeding and educaton suplementary feeding receiver after 1 month, 2 months, and after 3 months.Results : There was a difference nutritional status within   recovery suplementary feeding group  before and after receiving suplementary feeding p= 0.000. In recovery suplementary feeding group there was no significanly difference, p= 0.103. There was  no significant difference of nutritional status between group of recovery suplementary feeding receiver andeducation  suplementary feeding receiver after one month by p=0.706. and also after 2 months by p value = 0.063, but after 3 months there was significant difference by p value = 0.019. .Conclution : Nutritional status moalnourished children between the group of recovery suplementary feeding and educational suplementary feeding receiver was  significantly different after 3 months.